Method for manufacturing bonding sheets and bonded bodies
Patent Information
- Application Number
- JP2026175800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-16
Smart Images

Figure 2026169247000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a bonding sheet and a method for producing a bonded body.
Background Art
[0002] When two or more components are bonded together, for example, during assembly or mounting of electronic components, a bonding material may be used. For example, Patent Document 1 describes a bonding sheet formed by mixing copper particles and a solvent having a boiling point of 150°C or higher as a bonding material, and pressing the mixture at normal temperature.
Prior Art Literature
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] Such bonding sheets are required to appropriately bond members to each other.
[0005] The present invention has been made in view of the above, and an object thereof is to provide a bonding sheet capable of appropriately bonding members to each other, and a method for producing a bonded body.
Means for Solving the Problems
[0006] In order to solve the above-described problems and achieve the object, a bonding sheet according to the present disclosure includes a copper sintered body in which at least a part of first copper particles having an average particle diameter of 1 μm to 16 μm and second copper particles having an average particle diameter of 300 nm or less are sintered, and has a specific surface area of 0.16 m 2 / g to 2.44 m 2 / g, and a Young's modulus of 25 GPa or less.
[0007] The filling rate is preferably 45% to 60%.
[0008] It is preferable that the thermal conductivity is between 10 W / mK and 60 W / mK.
[0009] It is preferable that the content ratio of the first copper particles to the second copper particles is 5:95 to 40:60 in terms of volume ratio.
[0010] To solve the above-mentioned problems and achieve the objective, the method for manufacturing a joint according to the present disclosure includes the steps of: placing the joining sheet on a first member; placing a second member on the joining sheet to obtain a laminate in which the joining sheet is placed between the first member and the second member; and heating the laminate to manufacture a joint in which the first member and the second member are joined. [Effects of the Invention]
[0011] According to the present invention, members can be properly joined together. [Brief explanation of the drawing]
[0012] [Figure 1] Figure 1 is a schematic diagram of the bonding sheet according to this embodiment. [Figure 2] Figure 2 is a schematic, partially enlarged view of the bonding sheet. [Figure 3] Figure 3 is a flowchart illustrating the manufacturing method of the bonding sheet according to this embodiment. [Figure 4] Figure 4 is a schematic diagram illustrating the manufacturing method of the joint. [Figure 5] Figure 5 is a table showing the characteristics and evaluation results of the bonding sheets for each example. [Modes for carrying out the invention]
[0013] The present invention will now be described in detail with reference to the drawings. However, the present invention is not limited to the embodiments described below. Furthermore, the components in the embodiments below include those easily conceivable by those skilled in the art, those that are substantially identical, and those that fall within the so-called equivalent range. Moreover, the components disclosed in the embodiments below can be combined as appropriate.
[0014] (Bonding sheet) Figure 1 is a schematic diagram of the joining sheet according to this embodiment. The joining sheet 10 according to this embodiment is a sheet-like member that joins members together. The joining sheet 10 is made of copper. In this embodiment, the joining sheet 10 is a sintered copper body, and as shown in Figure 1, it has a structure in which a plurality of copper particles 12 are bonded together by sintering. It is preferable that the joining sheet 10 undergoes further sintering when heated at 150°C to 300°C. In other words, the joining sheet 10 can be said to be a partially sintered copper body. Here, the progression of sintering refers to an increase in the packing density as the bonding between the copper particles 12 progresses further. Since the joining sheet 10 is a partially sintered body, members can be properly joined together by advancing the sintering. Note that the joining sheet 10 only needs to contain a partially sintered copper body, and may contain some unsintered copper particles.
[0015] The bonding sheet 10 preferably has a filling rate of 45% to 60%, more preferably 50% to 60%, and even more preferably 50% to 55%. A filling rate within this range allows for a larger surface area, enabling proper sintering and thus proper bonding of the components. The packing density is the ratio of bulk density to true density (bulk density / true density). Here, true density refers to the density of the material itself (copper in this case), assuming that there are no pores or cracks in the sintered body, i.e., the theoretical density. Bulk density refers to the value obtained by dividing the weight of the bonding sheet 10 by the volume obtained from the external dimensions of the bonding sheet 10. The volume obtained from the external dimensions refers to the total volume of the bonding sheet 10, including the pores. True density is, for example, the literature value for the density of copper (e.g., 8.96 g / cm³). 3 ) can be used. In addition, bulk density can be measured using a balance, a coordinate measuring machine, and a micrometer. For example, the area and thickness of the bonding sheet 10 are measured using a coordinate measuring machine and a micrometer, and the value obtained by multiplying the area and thickness is taken as the volume obtained from the external dimensions. Then, the weight of the bonding sheet 10 is measured using a balance, and the value obtained by dividing the measured weight by the volume obtained from the external dimensions is taken as the bulk density. As described later, the bonding sheet 10 may be impregnated with resin in the copper sintered body. In this case, the filling rate refers to the filling rate of the copper sintered body excluding the resin. In subsequent descriptions of the properties of the bonding sheet 10 other than the filling rate, these may similarly refer to the properties of the copper sintered body excluding the resin.
[0016] The bonding sheet 10 has a main surface 10a on one side and a main surface 10b on the other side. The arithmetic mean roughness Ra is preferably 1 μm or more and 40 μm or less, more preferably 1 μm or more and 35 μm or less, and even more preferably 1 μm or more and 30 μm or less. The bonding sheet 10 may have an arithmetic mean roughness Ra of at least one of its surfaces 10a and 10b within the above range. When the arithmetic mean roughness Ra (surface roughness) is within this range, further sintering can proceed appropriately, and the components can be properly joined together. The arithmetic mean roughness Ra can be measured according to the provisions of JIS B 0601:2001.
[0017] Figure 2 is a schematic enlarged view of a part of the bonding sheet. As shown in Figures 1 and 2, the bonding sheet 10 includes first copper particles 12a and second copper particles 12b, which have a smaller diameter than the first copper particles 12a, as copper particles 12. In other words, the bonding sheet 10 can be said to include a sintered copper body in which at least a portion of the first copper particles 12a and the second copper particles 12b are sintered. The average particle size Da of the first copper particles 12a is 1 μm or more and 16 μm or less, preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 3 μm or less. The average particle size Db of the second copper particle 12b is 300 nm or less, preferably 100 nm to 300 nm, more preferably 150 nm to 300 nm, and even more preferably 200 nm to 250 nm. By including first copper particles 12a and second copper particles 12b whose average particle size is within this range, it is possible to suppress excessive sinterability and prevent the Young's modulus of the bonded layer from becoming too high after joining. This allows the material to deform appropriately to follow the shape of the components during joining, resulting in proper joining of the components. Furthermore, by including first copper particles 12a and second copper particles 12b whose average particle size is within this range, it is possible to suppress the occurrence of cracks due to volume shrinkage during sintering, resulting in proper joining of the components. In the bonding sheet 10, the copper particles 12 are bonded together by sintering. Therefore, the average particle size Da of the first copper particles 12a can be said to be the average particle size of the first copper particles 12a separated by the interface between the bonded copper particles 12 in the bonding sheet 10. Similarly, the average particle size Db of the second copper particles 12b can be said to be the average particle size of the second copper particles 12b separated by the interface between the bonded copper particles 12 in the bonding sheet 10. The average particle sizes Da and Db can be measured, for example, as follows: After sealing the bonding sheet with epoxy resin, the bonding sheet is cut horizontally to the thickness direction of the bonding sheet. The cross-section of the bonding sheet is prepared by mechanical polishing and cross-polishing the cut surface. Next, the cut surface of the bonding sheet is observed at 10,000x magnification using an SEM (scanning electron microscope), and 10 randomly taken SEM images are obtained. The obtained SEM images are binarized using image processing software (ImageJ from the National Institutes of Health, USA) to separate the particle portion and the void portion. In the particle portion, if at least some of the copper particles are sintered together to form a neck, the line segment with the minimum length when a line segment is drawn over each neck is used as the boundary of the copper particles. The particle size of each copper particle captured in the SEM image was measured, and copper particles with a particle size of 500 nm or more were extracted as first copper particles 12a, and copper particles with a particle size of less than 500 nm were extracted as second copper particles 12b. The average particle size of first copper particles 12a was defined as the average particle size Da of first copper particles 12a, and the average particle size of second copper particles 12 was defined as the average particle size Db of second copper particles 12b. Here, particle size refers to the diameter of a perfectly round particle obtained by measuring the number of pixels in the region of the copper particle using image processing software and converting it to a perfectly round particle with the same number of pixels.
[0018] The bonding sheet 10 preferably has a volume ratio of 5:95 to 40:60 between first copper particles 12a and second copper particles 12b, more preferably 10:90 to 35:65, even more preferably 15:85 to 30:70, and still more preferably 20:80 to 25:75. This ratio allows for proper bonding of the components. The content ratio can be measured using the following procedure. Specifically, the ratio Sa:Sb of the total region occupied by copper particles with an average particle size of 1 μm to 16 μm (copper particles with a particle size of 500 nm or more) and the total region occupied by copper particles with an average particle size of 300 nm or less (copper particles with a particle size of less than 500 nm) in the SEM image used to obtain the average particle size Da and average particle size Db may be used as the content ratio.
[0019] In the present embodiment, the bonding sheet 10 contains two types of copper particles 12 having different particle size distributions (average particle diameters), but the present invention is not limited thereto, and the bonding sheet 10 may contain three or more types of copper particles 12 having different particle size distributions (average particle diameters).
[0020] The bonding sheet 10 has a specific surface area of 0.16 m 2 / g or more and 2.44 m 2 / g or less, preferably 0.85 m 2 / g or more and 1.60 m 2 / g or less, more preferably 1.00 m 2 / g or more and 1.30 m 2 / g or less. When the specific surface area falls within this range, further sintering can be appropriately progressed, and the members can be properly bonded to each other. The specific surface area of the bonding sheet 10 can be determined by measuring the nitrogen gas adsorption amount of the bonding sheet 10 using a specific surface area measuring apparatus (QUANTACHROME AUTOSORB-1 manufactured by Quantachrome Instruments), and calculating by the BET method.
[0021] The bonding sheet 10 has a Young's modulus of 25 GPa or less, preferably 10 GPa or more and 20 GPa or less, and more preferably 12 GPa or more and 15 GPa or less. When the Young's modulus falls within this range, the risk of breakage can be suppressed. The Young's modulus can be measured using a Picodenter HM500 (manufactured by Fisher Instruments, analysis software: WIN-HCU ver.7.0), which is an apparatus compliant with ISO14577, the standard for the nanoindentation method. The nanoindentation method is a technique for calculating hardness and Young's modulus from the load applied to a sample and the indentation depth. In this embodiment, the Young's modulus of the bonding sheet 10 is defined as the average value of the indentation Young's modulus obtained when the upper surface of the bonding sheet 10 is measured a total of five times at five randomly selected locations using the apparatus and analysis software. The measurement conditions were as follows: the terminal was a Vickers indenter, the indentation depth was 2 μm, the indentation speed was 0.067 μm / sec, and the measurement temperature was 25°C. The bonding sheet 10 was measured while placed on a silicon wafer with a thickness of 0.4 mm, which is larger than the bonding sheet 10. Subsequent Young's moduli may also refer to measurements taken using the same method.
[0022] The bonding sheet 10 preferably has a thermal conductivity of 10 W / mK to 60 W / mK, more preferably 15 W / mK to 55 W / mK, and even more preferably 20 W / mK to 50 W / mK. A thermal conductivity within this range allows for effective transfer of heat between the members being bonded. Thermal conductivity can be determined, for example, by conversion from resistivity. Specifically, the sheet resistance of a 10mm x 10mm bonding sheet at 25°C is measured using a four-probe method with a Laurester (MCP-250T, manufactured by Mitsubishi Petrochemical Co., Ltd.), and the resistivity is calculated by multiplying this by the sheet thickness. The thermal conductivity at 25°C is determined by converting the resistivity using the Wiedemann-Franz law.
[0023] The bonding sheet 10 preferably has a thickness W of 0.1 mm or more and 1 mm or less, more preferably 0.2 mm or more and 0.7 mm or less, and even more preferably 0.3 mm or more and 0.5 mm or less. As shown in Figure 1, the thickness W refers to the distance in the thickness direction Z between the point on surface 10a that protrudes the most from surface 10a and the point on surface 10b that protrudes the most from surface 10b. Furthermore, the projected area when the bonding sheet 10 is projected in direction Z is 10,000 mm². 2 Preferably, it is 6400mm 2 The following is more preferable: 3600mm 2 The following is even more preferable: By using a bonding sheet 10 with a thickness W and projected area within this range, the components can be properly joined.
[0024] Furthermore, the value obtained by dividing the thickness W of the bonding sheet 10 by the filling rate (%) of the bonding sheet 10 (thickness W / filling rate) is defined as the large-area bonding index D1. In this case, the large-area bonding index D1 is preferably 1.50 or more and 10.0 or less, and more preferably 4.0 or more and 8.0 or less. When the large-area joining index D1 falls within this range, the members can be properly joined together.
[0025] The bonding sheet 10 may be a copper sintered body impregnated with resin. That is, the bonding sheet 10 may have resin filling at least a portion of its internal pores. Examples of resins include epoxy resin and silicone resin. By impregnating the bonding sheet 10 with resin, appropriate functions can be imparted to it.
[0026] (Method for manufacturing bonding sheets) Figure 3 is a flowchart illustrating the manufacturing method of the bonding sheet according to this embodiment.
[0027] (Preparation of copper particles) As shown in Figure 3, in this manufacturing method, copper particles 12A are first prepared (step S10). The copper particles 12A here are copper particles that will be used as raw materials for the bonding sheet 10, and can also be described as copper powder before pre-sintering. In other words, by pre-sintering the copper particles 12A, a bonding sheet 10 is produced in which the copper particles 12 are bonded together by pre-sintering. The copper particles before pre-sintering are copper particles 12A, and the copper particles after pre-sintering are copper particles 12. Furthermore, in this manufacturing method, copper particles 12A are prepared as first copper particles 12Aa and second copper particles 12Ba, which have a smaller diameter than the first copper particles 12Aa. The first copper particles 12Aa are the raw material for the first copper particles 12a, and the second copper particles 12Ba are the raw material for the second copper particles 12b.
[0028] The first copper particle 12Aa has a BET diameter of 1 μm or more and 16 μm or less, preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 3 μm or less. The second copper particle 12Ba has a BET diameter of 300 nm or less, preferably between 50 nm and 300 nm, more preferably between 80 nm and 200 nm, and even more preferably between 80 nm and 170 nm. The BET diameter of the first copper particle 12Aa and the second copper particle 12Ba being within this range prevents excessive sinterability from causing the Young's modulus of the bonded layer to become too high after joining. This allows the material to deform appropriately to follow the shape of the components during joining, resulting in proper joining of the components. Furthermore, by including first copper particles 12a and second copper particles 12b with average particle sizes within this range, the occurrence of cracks due to volume shrinkage during sintering can be suppressed, allowing for proper joining of the components. The BET diameter is the particle size calculated from the BET specific surface area and true density of the copper particles, which are determined by the BET method, assuming that the copper particles 12A are spherical or cubic. Specifically, it can be determined by the method described in the examples below.
[0029] The BET specific surface area of the first copper particle 12Aa is 0.04 m². 2 / g or more 0.67m 2 It is preferable that it be less than or equal to / g, and 0.07m 2 / g or more 0.67m 2 It is more preferable that it be less than or equal to / g, and 0.22m 2 / g or more 0.67m 2 It is even more preferable that the amount be less than or equal to / g. The BET specific surface area of the second copper particle 12Ba is 2.23 m². 2 / g or more 13.39m 2 It is preferable that the amount be less than or equal to 3.35m 2 / g or more 8.37m 2 It is more preferable that it be less than or equal to / g, and 3.93m 2 / g or more 8.37m 2 It is even more preferable that the amount be less than or equal to / g. Having a specific surface area within this range allows for proper sintering and effective joining of components. The shape of the copper particles 12A is not limited to spherical; it may also be needle-shaped or flattened.
[0030] It is preferable that the surface of the copper particles 12A is coated with an organic protective film, which is a film of organic matter. By being coated with an organic protective film, oxidation of the copper particles 12A is suppressed, and the decrease in sinterability due to oxidation of the copper particles 12A is further reduced. It should be said that the organic protective film coating the copper particles 12A is not formed by the solvent 20 and is not derived from the solvent 20. It can also be said that the organic protective film coating the copper particles 12A is not a film of copper oxide formed by the oxidation of copper.
[0031] The fact that copper particles 12A are coated with an organic protective film can be confirmed by analyzing the surface of copper particles 12A using time-of-flight secondary ion mass spectrometry (TOF-SIMS). Therefore, in this embodiment, copper particles 12A are detected by analyzing the surface using time-of-flight secondary ion mass spectrometry. + C3H3O3 relative to the amount of ions detected - Ratio of detected ions (C3H3O3) - / Cu + The ratio is preferably 0.001 or higher. C3H3O3 - / Cu + The ratio is more preferably within the range of 0.05 to 0.2. In this analysis, the surface of copper particles 12A refers to the surface of copper particles 12A including the covering organic protective film (i.e., the surface of the organic protective film), not the surface of copper particles 12A after the organic protective film has been removed.
[0032] Copper particle 12A was analyzed on its surface using time-of-flight secondary ion mass spectrometry to determine the presence of C3H4O2. - Ions and ions of C5 or higher may be detected. + C3H4O2 relative to the amount of ions detected - Ratio of detected ions (C3H4O2) - / Cu +The ratio is preferably 0.001 or higher. Also, Cu + Ratio of the amount of C5 or greater ions detected to the amount of ions detected (C5 or greater ions / Cu + The ratio is preferably less than 0.005.
[0033] C3H3O3 detected by time-of-flight secondary ion mass spectrometry - Ions and C3H4O2 - The ions and ions with C5 or higher originate from the organic protective film covering the surface of copper particle 12A. Therefore, C3H3O3 - / Cu + Ratio and C3H4O2 - / Cu + When each of the ratios is 0.001 or higher, the surface of the copper particles 12A becomes less susceptible to oxidation, and the copper particles 12A become less susceptible to aggregation. Also, C3H3O3 - / Cu + Ratio and C3H4O2 - / Cu + When the ratio is 0.2 or less, oxidation and aggregation of copper particles 12A can be suppressed without excessively reducing the sinterability of copper particles 12A, and the generation of decomposition gases of the organic protective film during heating can be suppressed, so that a bonding layer with fewer voids can be formed. To further improve the oxidation resistance of copper particles 12A during storage and to further improve the sinterability at low temperatures, C3H3O3 - / Cu + Ratio and C3H4O2 - / Cu + The ratio is preferably within the range of 0.08 to 0.16. Also, C5 or higher ions / Cu + If the ratio is 0.005 or higher, a large amount of organic protective film with a relatively high desorption temperature is present on the particle surface, resulting in insufficient sinterability and difficulty in obtaining a strong bonding layer. C5 or higher ions / Cu + The ratio is preferably less than 0.003 times.
[0034] The organic protective film is preferably derived from citric acid. A method for producing copper particles 12A coated with a citric acid-derived organic protective film will be described later. The amount of organic protective film coating on the copper particles 12A is preferably in the range of 0.5% to 2.0% by mass, more preferably in the range of 0.8% to 1.8% by mass, and even more preferably in the range of 0.8% to 1.5% by mass, based on 100% by mass of copper particles. By having an organic protective film coating amount of 0.5% by mass or more, the copper particles 12A can be uniformly coated with the organic protective film, and the oxidation of the copper particles 12A can be more reliably suppressed. Furthermore, by having an organic protective film coating amount of 2.0% by mass or less, it is possible to suppress the generation of voids in the sintered body (bonding layer) of copper particles due to gases generated by the decomposition of the organic protective film by heating. The amount of organic protective film coating can be measured using commercially available equipment. For example, the coating amount can be measured using a differential thermal balance TG8120-SL (manufactured by RIGAKU Corporation). In this case, for example, copper particles from which moisture has been removed by freeze-drying are used as the sample. To suppress oxidation of the copper particles, the measurement is performed in nitrogen (G2 grade) gas, the heating rate is set to 10°C / min, and the weight loss rate when heated from 250°C to 300°C can be defined as the amount of organic protective film coating. That is, coating amount = (weight of sample after measurement) / (weight of sample before measurement) × 100 (wt%). The measurement is performed three times for each batch of copper particles from the same lot, and the arithmetic mean may be used as the coating amount.
[0035] When copper particles 12A are heated at 300°C for 30 minutes under an inert gas atmosphere such as argon gas, it is preferable that 50% or more of the organic protective film decomposes. The organic protective film derived from citric acid generates carbon dioxide gas, nitrogen gas, acetone vapor, and water vapor during decomposition.
[0036] Copper particles 12A coated with a citric acid-derived organic protective film can be manufactured, for example, as follows. First, an aqueous dispersion of copper citrate is prepared, and a pH adjuster is added to this aqueous copper citrate dispersion to adjust the pH to between 2.0 and 7.5. Next, under an inert gas atmosphere, a hydrazine compound in an amount of 1.0 to 1.2 equivalents, capable of reducing copper ions, is added to this pH-adjusted aqueous copper citrate dispersion and mixed. The resulting mixture is heated to a temperature of 60°C to 80°C under an inert gas atmosphere and held for 1.5 to 2.5 hours. This reduces the copper ions eluted from the copper citrate to produce copper particles 12A, and also forms a citric acid-derived organic protective film on the surface of these copper particles 12A.
[0037] Aqueous dispersions of copper citrate can be prepared by adding powdered copper citrate to pure water such as distilled water or deionized water at a concentration of 25% to 40% by mass, stirring with a stirring blade, and dispersing it uniformly. Examples of pH adjusters include triammonium citrate, ammonium hydrogen citrate, and citric acid. Among these, triammonium citrate is preferred because it allows for mild pH adjustment. The pH of the aqueous copper citrate dispersion is set to 2.0 or higher to increase the elution rate of copper ions eluted from copper citrate, thereby accelerating the formation of copper particles and obtaining the target fine copper particles 12A. The pH is set to 7.5 or lower to suppress the formation of copper(II) hydroxide from the eluted copper ions, thereby increasing the yield of copper particles 12A. Furthermore, by setting the pH to 7.5 or lower, the reducing power of the hydrazine compound can be suppressed, making it easier to obtain the target copper particles 12A. It is preferable to adjust the pH of the copper citrate dispersion to a range of 4 to 6.
[0038] The reduction of copper citrate with hydrazine compounds is carried out under an inert gas atmosphere. This is to prevent the oxidation of copper ions dissolved in the liquid. Examples of inert gases include nitrogen gas and argon gas. Hydrazine compounds have advantages such as not producing residue after the reduction reaction when reducing copper citrate under acidic conditions, being relatively safe, and being easy to handle. Examples of hydrazine compounds include hydrazine monohydrate, anhydrous hydrazine, hydrazine hydrochloride, and hydrazine sulfate. Among these hydrazine compounds, hydrazine monohydrate and anhydrous hydrazine, which do not contain components that can become impurities such as sulfur and chlorine, are preferred.
[0039] Generally, copper generated in acidic solutions with a pH below 7 dissolves. However, in this embodiment, a hydrazine compound, which is a reducing agent, is added to an acidic solution with a pH below 7 and mixed, generating copper particles 12A in the resulting mixture. As a result, the citric acid-derived components generated from copper citrate quickly coat the surface of the copper particles 12A, thereby suppressing the dissolution of the copper particles 12A. It is preferable to raise the aqueous dispersion of copper citrate, after adjusting the pH, to a temperature of 50°C to 70°C to facilitate the reduction reaction.
[0040] The mixture of copper particles 12A and hydrazine compounds is heated to a temperature of 60°C to 80°C under an inert gas atmosphere and held for 1.5 hours to 2.5 hours in order to generate copper particles 12A and to form and coat an organic protective film on the surface of the generated copper particles 12A. The heating and holding under an inert gas atmosphere is to prevent oxidation of the generated copper particles 12A. The starting material, copper citrate, usually contains about 35% by mass of copper. By adding a hydrazine compound, which is a reducing agent, to a copper citrate aqueous dispersion containing this amount of copper, heating it to the above temperature, and holding it for the above time, the generation of copper particles 12A and the formation of an organic protective film on the surface of the copper particles 12A proceed in a balanced manner, so that copper particles 12A can be obtained in which the amount of organic protective film covering is in the range of 0.5% by mass to 2.0% by mass per 100% by mass of copper particles. If the heating temperature is below 60°C and the holding time is less than 1.5 hours, the copper citrate may not be completely reduced, resulting in a slower rate of copper particle 12A formation and potentially an excessive amount of organic protective film coating the copper particles 12A. Conversely, if the heating temperature exceeds 80°C and the holding time exceeds 2.5 hours, the rate of copper particle 12A formation may be too fast, potentially resulting in an insufficient amount of organic protective film coating the copper particles 12A. The preferred heating temperature is between 65°C and 75°C, and the preferred holding time is between 2 hours and 2.5 hours.
[0041] The copper particles 12A generated in the mixture are separated from the mixture using, for example, a centrifuge under an inert gas atmosphere, and then dried by freeze-drying or vacuum drying to obtain copper particles 12A whose surface is coated with an organic protective film. Because the surface of these copper particles 12A is coated with an organic protective film, they are less susceptible to oxidation even when stored in the atmosphere until they are used as a bonding sheet 10.
[0042] (Filling the mold with copper particles) Next, as shown in Figure 3, the prepared copper particles 12A (first copper particles 12Aa and second copper particles 12Ba) are mixed and filled into a mold (step S12). The shape and material of the mold into which the copper particles 12A are filled can be arbitrary.
[0043] When mixing the first copper particles 12Aa and the second copper particles 12Ab, the addition ratio of the first copper particles 12Aa to the second copper particles 12Ab is preferably 5:95 to 40:60 by volume, preferably 10:90 to 35:65, more preferably 15:85 to 30:70, and even more preferably 20:80 to 25:75. By setting the addition ratio within this range, the components can be properly joined together.
[0044] (Pre-sintering of copper particles) Next, the copper particles 12A (a mixture of first copper particles 12Aa and second copper particles 12Ba) filled in the mold are pressurized at a predetermined temperature to pre-sinter the copper particles 12A, thereby generating the bonding sheet 10 (step S14). In this step, the copper particles 12A filled in the mold are pressurized at a predetermined pressure and held at a predetermined temperature for a predetermined time to pre-sinter the copper particles 12A and generate the bonding sheet 10. The predetermined pressure here is preferably 10 MPa to 30 MPa, more preferably 11 MPa to 25 MPa, and even more preferably 12 MPa to 20 MPa. The predetermined temperature here is preferably 150°C to 250°C, more preferably 160°C to 240°C, and even more preferably 170°C to 230°C. The predetermined time here (the time for holding at a predetermined pressure and temperature) is preferably 1 minute or more and 30 minutes or less, more preferably 2 minutes or more and 25 minutes or less, and even more preferably 3 minutes or more and 20 minutes or less. By pre-sintering the copper particles 12A under these conditions, a bonding sheet 10 capable of properly joining components can be manufactured appropriately.
[0045] Furthermore, the bonding sheet 10 is not limited to being manufactured by the method described above, and the manufacturing method of the bonding sheet 10 may be arbitrary.
[0046] (Method of manufacturing the joint) Next, a method for manufacturing a bonded body 100 by joining members together using a bonding sheet 10 will be described. Figure 4 is a schematic diagram illustrating the manufacturing method of a bonded body. In this embodiment, a bonded body 100 is manufactured by joining a first member A and a second member B using a bonding sheet 10 as a bonding layer. The first member A and the second member B can be any material, but for example, one of the first member A and the second base material B may be a substrate and the other may be an electronic component. That is, a semiconductor module in which a substrate and an electronic component are joined by a bonding layer may be manufactured as the bonded body 100. The substrate is not particularly limited, but examples include oxygen-free copper plates, copper-molybdenum plates, high heat dissipation insulating substrates (e.g., DCB (Direct Copper Bond)), and substrates for mounting semiconductor elements such as LED (Light Emitting Diode) packages. Examples of electronic components include semiconductor devices such as IGBTs (Insulated Gate Bipolar Transistors), diodes, Schottky barrier diodes, MOS-FETs (Metal Oxide Semiconductor Field Effect Transistors), thyristors, logic circuits, sensors, analog integrated circuits, LEDs, semiconductor lasers, and oscillators.
[0047] In this manufacturing method, as shown in step S20 of Figure 4, the bonding sheet 10 is placed on the surface of the first member A. In the example of Figure 4, the bonding sheet 10 is placed on the first member A such that the surface 10b of the bonding sheet 10 is in contact with the surface of the first member A.
[0048] Next, as shown in step S22, solvent 20 is applied to the surface 10a of the bonding sheet 10 (the surface not in contact with the first member A). Solvent 20 acts as a binder for the copper particles 12. Solvent 20 is an organic solvent. Note that the addition of solvent 20 is not essential.
[0049] The solvent 20 preferably has a boiling point of 150°C or higher, and more preferably 200°C or lower. The boiling point of solvent 20 is more preferably 150°C to 300°C, and even more preferably 200°C to 250°C. Furthermore, the solvent 20 preferably has a molecular weight in the range of 100 to 1000, more preferably 200 to 800, and particularly preferably 200 to 600. In addition, the solvent is preferably a compound having a reducing group at its terminus. The reducing group is preferably a hydroxyl group. Furthermore, the dielectric constant of solvent 20 preferably has a dielectric constant of 4 to 80, more preferably 10 to 45, and even more preferably 20 to 40. The dielectric constant may be measured using a dielectric constant meter for liquids (Model 871, manufactured by Nippon Luft Co., Ltd.).
[0050] As the solvent 20, for example, diol compounds and triol compounds can be used. Examples of diol compounds include ethylene glycol, diethylene glycol, and polyethylene glycol. Examples of triol compounds include glycerin, butanetriol, and polyoxypropylenetriol. These organic solvents and polymeric solvents may be used individually or in combination of two or more.
[0051] The solvent 20 is preferably added to the bonding sheet 10 in an amount of 0.5% to 10% by mass, preferably 1% to 8%, and more preferably 2% to 5%. By adding solvent 20 within this range, the bonding properties can be appropriately maintained.
[0052] As shown in step S24, the solvent 20 penetrates into the pores of the bonding sheet 10 and fills them. In other words, the bonding sheet 10 becomes impregnated with the solvent 20.
[0053] Subsequently, as shown in step S26, the second member B is placed on the surface 10a of the bonding sheet 10 impregnated with solvent 20. That is, the bonding sheet 10 impregnated with solvent 20 is placed between the first member A and the second member B.
[0054] Subsequently, the laminate in which the bonding sheet 10 is placed between the first member A and the second member B is heated to further advance the sintering of the bonding sheet 10, thereby generating a bonded body 100 in which the first member A and the second member B are joined by a bonding layer (sintered bonding sheet 10). The heating temperature of the laminate may be, for example, in the range of 150°C to 300°C. The heating time of the laminate may be, for example, in the range of 10 minutes to 1 hour. It is preferable to heat the laminate under an inert gas atmosphere while pressurizing the laminate in the lamination direction. Nitrogen gas and argon gas can be used as the inert gas. It is preferable that the pressurizing pressure of the laminate be in the range of 0.5 MPa to 30 MPa.
[0055] (effect) As described above, the bonding sheet 10 according to this embodiment includes a sintered copper body in which at least a portion of first copper particles 12a with an average particle size of 1 μm or more and 16 μm or less and second copper particles 12b with an average particle size of 300 nm or less are sintered, and the specific surface area is 0.16 m². 2 / g or more 2.44m 2 The particle size is less than or equal to / g, and the Young's modulus is 25 GPa or less. The bonding sheet 10 according to this embodiment is a pre-sintered body of first copper particles 12a and second copper particles 12b within this average particle size range. By having a specific surface area and Young's modulus within this range, it is possible to suppress excessive sinterability and prevent the Young's modulus of the bonded layer from becoming too high after bonding. This allows the sheet to deform appropriately to follow the members during bonding, enabling proper bonding of the members. Furthermore, it is possible to suppress the occurrence of cracks due to volume shrinkage during sintering, enabling proper bonding of the members.
[0056] In this embodiment, the bonding sheet 10 preferably has a filling rate of 45% to 60%. A filling rate within this range allows for proper further sintering and effective bonding of the components.
[0057] In this embodiment, the bonding sheet 10 preferably has a thermal conductivity of 10 W / mK or more and 60 W / mK or less. Having a thermal conductivity within this range ensures adequate heat transfer of the bonded body 100.
[0058] In this embodiment, the bonding sheet 10 preferably has a volume ratio of 5:95 to 40:60 (5:95 or more and 40:60 or less) of first copper particles 12a to second copper particles 12b. This ratio allows for proper bonding of the components.
[0059] The method for manufacturing the joined body 100 according to this embodiment includes the steps of: placing a bonding sheet 10 on a first member A; placing a second member B on the bonding sheet 10 to obtain a laminate in which the bonding sheet 10 is placed between the first member and the second member; and heating the laminate to manufacture a joined body 100 in which the first member A and the second member B are joined. According to this manufacturing method, the joined body 100 can be properly manufactured by using the bonding sheet 10.
[0060] (Examples) Next, we will describe the examples. Figure 5 is a table showing the characteristics and evaluation results of the bonding sheets for each example.
[0061] (Example 1) (Preparation of copper particles) In Example 1, copper citrate 2.5-hydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and ion-exchanged water were stirred and mixed using a stirring blade to prepare a 30% by mass aqueous dispersion of copper citrate. Next, an aqueous solution of ammonium citrate was added to the obtained aqueous dispersion of copper citrate as a pH adjuster to adjust the pH of the dispersion to 5. Then, the obtained aqueous dispersion of copper citrate was heated to 50°C, and while maintaining that temperature, an aqueous solution of hydrazine monohydrate (diluted 2-fold) as a copper ion reducing agent was added all at once under a nitrogen gas atmosphere, and the mixture was stirred and mixed using a stirring blade. The amount of aqueous hydrazine monohydrate added was 1.2 times the equivalent amount required to reduce the total amount of copper ions. The obtained mixture was heated to 70°C under a nitrogen gas atmosphere and maintained at that temperature for 2 hours to generate copper particles. The generated copper particles were recovered using a centrifuge. The recovered copper particles were dried using a reduced-pressure drying method to produce first-order copper particles and second-order copper particles.
[0062] A specific surface area measuring device (QUANTACHROME AUTOSORB-1, manufactured by Quantachrome Instruments) was used. After removing adsorbed gas by degassing at a temperature of 50°C for 60 minutes, the amount of nitrogen gas adsorbed by the first and second copper particles was measured, and the specific surface area of the copper particles was determined by the BET method. The obtained specific surface area S(m²) was calculated as follows: 2 ( / g) and the density of copper particles ρ (g / cm³) 3 Using the following formula, the BET diameters of the first and second copper particles were calculated. BET diameter (nm) = 6000 / (ρ(g / cm) 3 ) × S(m 2 / g))
[0063] (Generation of bonding sheets) An aluminum frame with outer dimensions of 50mm x 50mm and an inner dimension of 30mm x 30mm with a hole was prepared as a mold for filling the prepared copper particles. The first and second copper particles were filled into this aluminum frame with an addition ratio of 25:75, and the total weight was 1.5g. The mixture was then leveled uniformly with a 30mm x 20mm aluminum block, and then hot-pressed in air at an applied pressure of 30MPa and a heating temperature of 150℃ for 15 minutes to produce a bonding sheet. The hot-pressing device used was a CYPT-50kN (manufactured by Shinto Kogyo Co., Ltd.). After the hot-pressing process, the material was cooled to room temperature, and the 30mm x 0.4mm bonding sheet sandwiched between the aluminum blocks was peeled off the aluminum blocks to obtain the desired bonding sheet.
[0064] (Characteristics of bonding sheets) The Young's modulus of the bonding sheet was measured using a picodenter. The method for measuring Young's modulus was the one described in this embodiment. Furthermore, the filling density of the bonding sheet was measured. The filling density was measured as follows: The volume obtained from the external dimensions of the bonding sheet was measured using calipers and a micrometer. Specifically, five points were randomly measured on each of the two horizontal sides of the bonding sheet, and the product of the average values was taken as the area of the bonding sheet. In addition, the thickness of the bonding sheet was measured randomly at 10 points using a micrometer, and the average value was taken as the thickness of the bonding sheet. The product of the area and thickness was taken as the volume obtained from the external dimensions of the bonding sheet. Next, the weight of the bonding sheet was measured. Then, the bulk density was calculated by dividing the weight of the bonding sheet by the volume obtained from the external dimensions of bonding sheet 10. The volume obtained from the external dimensions refers to the total volume of bonding sheet 10, including the pores. The true density was then 8.96 g / cm³. 3 The ratio of bulk density to true density was calculated as the packing efficiency. Furthermore, the specific surface area of the bonding sheet was measured. The specific surface area was measured as follows: Using a specific surface area measuring device (QUANTACHROME AUTOSORB-1, manufactured by Quantachrome Instruments), the amount of nitrogen gas adsorbed on the bonding sheet 10 was measured, and the specific surface area of the bonding sheet 10 was determined by the BET method. Nine bonding sheets cut into 10 mm squares were used for one measurement, and degassing treatment before measurement was performed at 50°C for 60 minutes. Furthermore, the average particle size of the first and second copper particles, and the content ratio (volume ratio) of the first and second copper particles in the bonding sheet were measured. The average particle sizes of the first and second copper particles were measured as follows: After sealing the bonding sheet with epoxy resin, the bonding sheet was cut horizontally to the thickness direction. The cross-section of the bonding sheet was prepared by mechanical polishing and cross-polishing the cut surface. Next, the cut surface of the bonding sheet was observed at 10,000x magnification using an SEM (scanning electron microscope), and multiple images were taken randomly to obtain an SEM image showing a total of 50 first copper particles. The obtained SEM image was binarized using image processing software (ImageJ from the National Institutes of Health, USA) to separate it into particle areas and void areas. In the particle areas, if at least a portion of the copper particles were sintered together to form a neck, the boundary of the copper particle was defined as the line segment with the minimum length when a line segment was drawn over each neck. The particle size of each copper particle captured in copper particle 12 was measured, and copper particles with a particle size of 500 nm or more were extracted as first copper particles, and copper particles with a particle size of less than 500 nm were extracted as second copper particles. The average particle size of the first copper particles was taken as the average particle size of the first copper particles, and the average particle size of the second copper particles 12 was taken as the average particle size of the second copper particles. Here, particle size refers to the diameter of a perfectly round particle obtained by randomly selecting a total of 50 copper particle regions from randomly captured SEM images, measuring the number of pixels for each using image processing software, and converting it to a perfectly round particle with the same number of pixels. The content ratio (volume ratio) of the first and second copper particles was measured as follows: In the SEM image obtained to obtain the particle size, the content ratio Sa:Sb was calculated as the ratio of the total region Sa occupied by copper particles with a particle size of 500 nm or more to the total region Sb occupied by copper particles with a particle size of less than 500 nm. Furthermore, the thermal conductivity of the bonding sheet was measured. Specifically, the sheet resistance of a 10mm x 10mm bonding sheet at 25°C was measured using a four-probe method with a Laurester (MCP-250T, manufactured by Mitsubishi Petrochemical Co., Ltd.), and the resistivity was calculated by multiplying this by the sheet thickness. The thermal conductivity at 25°C was then determined by converting the resistivity using the Wiedemann-Franz law. Figure 5 shows the measured values for Young's modulus, packing efficiency, specific surface area, average particle size, content ratio, and thermal conductivity.
[0065] (Examples 2-6) In Examples 2-6, the bonding sheets were produced in the same manner as in Example 1, except that the average particle size of the first copper particles, the average particle size of the second copper particles, the content ratio of the first and second copper particles, and the conditions for producing the bonding sheets were changed as shown in Figure 5. The measured values for Young's modulus, filling density, specific surface area, average particle size, content ratio, and thermal conductivity are shown in Figure 5.
[0066] (Comparative Examples 1-4) In Comparative Examples 1-4, the bonding sheets were produced in the same manner as in Example 1, except that the average particle size of the first copper particles, the average particle size of the second copper particles, the content ratio of the first and second copper particles, and the conditions for producing the bonding sheets were changed as shown in Figure 5. The measured values for Young's modulus, filling density, specific surface area, average particle size, content ratio, and thermal conductivity are shown in Figure 5. In Comparative Example 3, when measuring the average particle size, copper particles with a particle size greater than 10 μm were extracted as first copper particles, and copper particles with a particle size less than 10 μm were extracted as second copper particles.
[0067] (evaluation) For each example, a bonded structure was fabricated by joining components using a bonding sheet, and the shear strength of the bonded structure was evaluated. The bonding sheet for each example was cut using a commercially available utility knife to create bonding sheet pieces (2.5 mm square × 500 μm thick). These bonding sheet pieces (2.5 mm square × 500 μm thick) were placed on a 30 mm square × 1 mm thick oxygen-free copper substrate. Next, polyethylene glycol was applied as a solvent to the bonding sheet piece at a rate of 0.05 g per 0.95 g of sheet piece weight to impregnate it, and then a 2.5 mm square × 1 mm thick oxygen-free copper dummy element was placed on top. In this way, a laminate was obtained in which the oxygen-free copper substrate and the oxygen-free copper dummy element were laminated via the bonding sheet piece. The resulting laminate was used to create a bonded structure (Sample A) in which a 2.5 mm square oxygen-free copper substrate and an oxygen-free copper dummy element were bonded via a copper junction layer by holding the resulting laminate under conditions of nitrogen gas atmosphere, pressurization pressure of 5 MPa, and temperature of 250°C for 15 minutes using a die bonder (HTB-MM, manufactured by Alpha Design Co., Ltd.).
[0068] The shear strength of the resulting joint (Sample A) was measured according to the method specified in JIS Z 3198-7 (Lead-free solder test method - Part 7: Shear test method for solder joints of chip components). Specifically, a load was applied to an oxygen-free copper dummy element using a bond tester (Nordson DAGE, SERIES 4000), and the load (maximum shear load) at which the oxygen-free copper dummy element delaminated from the copper bonding layer was measured. The tool's movement speed was set to 50 μm / sec, and the gap between the tool tip and the oxygen-free copper substrate was set to 50 μm. The obtained maximum shear load was converted to Newtons and divided by the area of the copper bonding layer (2.5 mm × 2.5 mm) to obtain the shear strength (unit: MPa). Seven joints were fabricated, and the shear strength of each joint was measured. The results are shown in Figure 5.
[0069] In this evaluation, a shear strength of 30 MPa or higher was marked as ○ (pass), and a shear strength of less than 30 MPa was marked as × (fail). As shown in Figure 5, the sintered body consists of first copper particles with an average particle size of 1 μm to 16 μm and second copper particles with an average particle size of 300 nm or less, a Young's modulus of 25 GPa or less, and a specific surface area of 0.16 m². 2 / g or more 2.44m 2 When using the bonding sheet of the example with a yield of 0.2 / g or less, the shear strength of the bonded body is high, and proper bonding can be achieved. On the other hand, when using the bonding sheet of the comparative example that does not satisfy at least one of the above conditions, the shear strength of the bonded body is low, and proper bonding cannot be achieved.
[0070] (Evaluation of options) As an evaluation of the option, the density of the bonding layer in a bonded body manufactured using a bonding sheet was measured. The bonding sheet was cut using a commercially available utility knife to create bonding sheet pieces (10 mm square × 500 μm thick). The bonding sheet pieces (10 mm square × 500 μm thick) were placed on a 30 mm square × 1 mm thick oxygen-free copper substrate. Next, polyethylene glycol was applied as a solvent to the bonding sheet pieces at a rate of 0.05 g per 0.95 g of sheet weight to impregnate them, and then a 10 mm square × 1 mm thick oxygen-free copper dummy element was placed on top. In this way, a laminate was obtained in which the oxygen-free copper substrate and the oxygen-free copper dummy element were laminated via the bonding sheet pieces. The resulting laminate was used to fabricate a bonded structure (Sample B) in which a 2.5 mm square oxygen-free copper substrate and an oxygen-free copper dummy element were bonded via a copper junction layer by holding the bonded structure under conditions of 5 MPa pressure and 250°C temperature in a nitrogen gas atmosphere for 15 minutes using a die bonder (HTB-MM, manufactured by Alpha Design Co., Ltd.).
[0071] The copper bonding layer portion of the obtained bonded body (Sample B) was subjected to ultrasonic testing using an ultrasonic flaw detection device (Hitachi High-Technologies Corporation, FINE-SAT) to measure ultrasonic flaw detection images. The obtained ultrasonic flaw detection images were binarized using image processing software (ImageJ, National Institutes of Health, USA) to separate voids (cavities) from the bonded body (copper particle sintered body), and the void ratio was calculated using the following formula. Void ratio (%) = (Total area of voids / Area of copper bonding layer (10mm x 10mm)) x 100
[0072] Seven joints were fabricated, and the void ratio was measured for each joint. The results are shown in Figure 5.
[0073] Although embodiments of the present invention have been described above, the embodiments are not limited to those described herein. Furthermore, the aforementioned components include those that can be easily conceived by those skilled in the art, those that are substantially the same, and those that fall within the so-called equivalent range. Moreover, the aforementioned components can be combined as appropriate. Furthermore, various omissions, substitutions, or modifications of the components can be made without departing from the spirit of the embodiments described above. [Explanation of symbols]
[0074] 10 Bonding sheets 12 copper particles 12a Cuprous particles 12b Cupric particles 20 Solvents
Claims
1. The copper sintered body contains at least a portion of first copper particles with an average particle size of 1 μm to 16 μm and second copper particles with an average particle size of 300 nm or less, and has a specific surface area of 0.16 m². 2 / g or more 2.44m 2 A bonding sheet having a density of less than or equal to / g, a Young's modulus of 25 GPa or less, and an arithmetic mean surface roughness Ra of 1 μm or more and 40 μm or less.
2. The bonding sheet according to claim 1, wherein the average particle size of the first copper particles is 3 μm or less.
3. The bonding sheet according to claim 2, wherein the average particle size of the first copper particles is 1.7 μm or less.
4. A bonding sheet according to any one of claims 1 to 3, wherein the filling rate is 45% or more and 60% or less.
5. A bonding sheet according to any one of claims 1 to 4, wherein the thermal conductivity is 10 W / mK or more and 60 W / mK or less.
6. The bonding sheet according to any one of claims 1 to 5, wherein the content ratio of the first copper particles to the second copper particles is 5:95 to 40:60 by volume.
7. The steps of placing the bonding sheet according to any one of claims 1 to 6 on the first member, The steps include: placing a second member on the bonding sheet to obtain a laminate in which the bonding sheet is placed between the first member and the second member; A step of manufacturing a joint in which the first member and the second member are joined by heating the laminate, including, A method for manufacturing a composite body.
Citation Information
Patent Citations
Sheet for joining
JP2021116463A